PENGARUH CUSTOMER EXPERIENCE TERHADAP LOYALITAS PELANGGAN DENGAN E-WOM DAN KEPUASAN PELANGGAN SEBAGAI MEDIASI PADA TOKOPEDIA DI BALI - I Komang Ricky Satya Subagia; I Gusti Ayu Tirtayani (Berajah Journal, 2026)
The rapid growth of e-commerce in Indonesia has intensified competition among marketplace platforms in retaining customer loyalty. This study aims to examine the effect of customer experience on customer loyalty, with electronic word-of-mouth (e-WOM) and customer satisfaction serving as mediating variables among Tokopedia users in Bali. A quantitative research approach was employed using a survey method involving 200 active Tokopedia users in Bali. Respondents were selected through purposive sampling, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The findings reveal that customer experience has a positive and significant effect on e-WOM (β = 0.621; p < 0.001), customer satisfaction (β = 0.640; p < 0.001), and customer loyalty (β = 0.376; p < 0.001). Furthermore, e-WOM (β = 0.314; p < 0.001) and customer satisfaction (β = 0.278; p < 0.001) were found to have positive and significant effects on customer loyalty. The mediation analysis indicates that both e-WOM and customer satisfaction partially mediate the relationship between customer experience and customer loyalty. These findings demonstrate that a positive customer experience not only enhances customer satisfaction and positive online communication but also strengthens customer loyalty toward Tokopedia. Therefore, optimizing customer experience is a crucial strategic approach for marketplace platforms seeking to establish long-term relationships with consumers in an increasingly competitive digital environment.